Garut (Marantha Arundinaceae L.) Starch-Based Cookies with Rice Bran and Whole Wheat Flour as a Source of Fiber - Rofi’ul Kifayah; Basori Basori (Universitas Muhammadiyah Sidoarjo, 2015)
The escalation of degenerative diseases can be prevented by consuming fibrous foods. This study focus onproduct development of cookies from arrowroot starch with the addition of rice bran and whole wheat flour as fiber source. The addition of fiber was conductedusing various concentration of 0-30%. Aim of this study was determinedto add therice bran and whole wheat flour against physical-chemical properties of cookies. The data of physical-chemical properties were analyzed by Anova, followed by HSD test, while the organoleptic data were analyzed using Friedman test and determining the best treatment using method effectiveness index (De Garmo). Best quality wasshowedon proportion of20% rice bran flour (P2) and 20% whole wheat (P5) with the average value of the water content in sequence P2 and P5 are: 2.50% and 2.67%, 1.44% and dietary fiber 1.67%, 8.35% protein and 57.12%, and 60.73% texture and 65.80%. Organoleptic datashowedpreferable panelist on the color scale of 3.69 (regular) and 4.8 (a bit like), a sense of scale 4.13 (regular) and 4.77 (a bit like), aroma scale of 4.57 (slightly like) and 4.73 (a bit like), and the texture scale 4.37 (regular) and 4.33 (regular).